The Link between Human Papillomavirus and Prostate Cancer; A Narrative Literature Review - Rafighi, Dorna; Samenezhad, Sina; Khodadadeh Jigheh, Ali; Samenezhad, Hasti; Khodadadeh Jigheh, Fatemeh (Archives of Men’s Health, 2025)
Prostate cancer (PCa) remains a leading cause of cancer mortality in men globally. Age, genetic predisposition, and inflammation are the major risk factors. Increasing evidence suggests that oncogenic viruses, HPV types 16/18, could be involved in prostate carcinogenesis. This review critically examines the potential association between HPV infection and prostate cancer, including both molecular mechanisms and epidemiological evidence. We conducted a narrative literature review by systematically searching PubMed, Scopus, and Google Scholar for papers published from 2013 to 2025. We used search terms such as prostate cancer, HPV, oncogenic viruses, and viral carcinogenesis. We reviewed several peer-reviewed papers that involved molecular information, clinical documentation, and meta-analytic data. The evidence reports HPV DNA in 15-36% of PCa tissues, the most common being HPV-16/18. Mechanistically, HPV proteins (E6/E7) inactivate central tumor suppressors (p53, Rb), activate anti-apoptotic proteins (Bcl-2, survivin), and induce changes associated with cancer onset (through N-cadherin/TWIST), as observed in HPV-positive anogenital cancers. Genomic signatures reveal that HPV-positive PCa has characteristic patterns of mutation (e.g., KMT2C/D disruption). Nonetheless, heterogeneity across HPV detection assays and small sample sizes in a few studies call for cautious interpretation. Today, we have data suggesting that HPV may cause PCa, possibly through inflammation (NF-κB) and unstable genes; however, the exact mechanism remains unclear. We require large trials in many centers and additional screens to determine the role of HPV in this. As we can prevent HPV, these findings suggest that HPV vaccines could be of critical importance in preventing PCa. We must find out more.